The doubter's doubt about science and religion : or, in defence : a plea for the faith - Anderson, Robert, 1841-1918 (London, UK Pickering and Inglis)
Includes bibliographical references and index.
Brethren writer.
Keywords: Evolution -- religious aspects -- Christianity; Apologetics